Existent state and prospective directions of physical training improvement in Land Forces - Romanchuk S.V; Boyarchuk A.M; Romanchuk V.N (Kharkov National Pedagogical University, 2010)
Dependence of battle training of servicemen on the level of their physical training is considered at the paper. 284 officers, 63 sergeants took part in the research and 1788 school-leavers analyzed the results. According to the results it is researched the level of physical preparedness of school-leavers, level of methodological preparedness of supervisors and process of organization of physical training. The direction of improvement of physical training system is suggested according to these results. The level of physical preparedness of university entrants, level of methodical preparedness of leaders and process of organization of physical preparation, is investigational. Directions of improvement of the system of physical preparation are offered. The necessity of including of physical preparation is set for a teaching and educational process taking into account rational stage of preparation of soldiery specialists.